Vivências de leitura e escrita em língua portuguesa por surdos graduados - Pereira, Miriam Maia de Araújo (2018)
This research aims to investigate the relationship between writing in Portuguese language and the deaf subject inserted in formal education. As well as trying to understand how this relationship occurs in the writing process of those who have completed graduation and those who are supposed to be proficient in reading and have the ability to write. The specific objectives are: to analyze the written productions of the deaf subjects; to investigate the influence of Libras in the written production, in Portuguese, of the deaf; to verify how the schooling of the deaf collaborated to acquire their writing in Portuguese. The theoretical foundation is based in approaches of inclusion policies (BRAZIL, 1988/2015), in Bilingualism (GOLDFELD, 1997; SACKS, 1998; QUADROS, 2012; BOTELHO, 2013 and SKLIAR, 2001), in a socio-historical (VYGOTSKY, 2000) and dialogic perspective (BAKHTIN, 2010). It is a case study (LÜDKE AND ANDRE, 2015) in a qualitative methodology (CHIZZOTTI, 2014), with interpretative orientation (MOITA-LOPES, 1994). The participants are two deaf graduates, living in the city of Macapá, in the State of Amapá. Data generation was done through questionnaire (GIL, 2008), textual production (GERALDI, 2003), reading experiences (ZANOTTO, 1995), the reflective journal (SOARES, 2006) and interview (GIL, 2008). The data revealed that the relationship of these deaf subjects to writing in Portuguese is complex, since even after years of schooling they cannot express themselves efficiently through writing. It demonstrates that the educational process in which they were inserted disregarded their linguistic specificities, depriving them of a teaching based on a bilingual proposal, in which the Libras should be the way of access to the knowledge in Portuguese language, thus enabling them to be active and responsive subjects in relation to their learning